Impact of Displacement on Mental Health Among Elderly War Victims in Syam - Nurzahara Sihombing; M. Agung Rahmadi; Helsa Nasution; Luthfiah Mawar (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This study comprehensively evaluates the impact of displacement on the mental health of the elderly population affected by armed conflict in the Syam region through a systematic review and meta-analysis of 47 empirical studies (N=12,483) published between 2011 and 2024. The meta-analytic findings indicate an exceptionally high prevalence of severe psychological disorders within this population, with PTSD recorded at 63.8% (95% CI [59.2–68.4]), major depression at 58.2% (95% CI [54.1–62.3]), and generalized anxiety disorder at 52.4% (95% CI [48.3–56.5]). Multilevel regression analysis identified the duration of displacement (β=0.42, p<.001) and the loss of family support (β=0.38, p<.001) as the most significant determinants of the elevated prevalence of these mental health disorders. In particular, elderly individuals who experienced displacement for more than three years exhibited a 2.8-fold increased risk of developing psychological disorders compared to those displaced for less than one year (OR=2.83, 95% CI [2.41–3.25]). Findings from the meta-regression further revealed that social support (r=–0.45, p<.001) and adequate access to mental health services (r=–0.38, p<.001) served as significant protective factors. Accordingly, these results not only extend the contributions of prior studies by Peconga & Høgh Thøgersen (2020) and Chung et al. (2018) but also uncover the complex interaction between the duration of displacement and the degradation of social networks as key determinants within the mental health dynamic. Furthermore, this study makes an original contribution by identifying psychosocial adaptation patterns among elderly refugees that are structurally distinct from those of the general population while simultaneously proposing a contextually designed community-based intervention framework to address the multidimensional needs of elderly war victims.